Elevated Ribonucleotide Reductase Levels Associate With Suppressed Radiochemotherapy Response in Human Cervical Cancers. Issue 9 (1st November 2012) - Kunos, Charles A.; Radivoyevitch, Tomas; Kresak, Adam; Dawson, Dawn; Jacobberger, James; Yang, Bin; Abdul-Karim, Fadi W.
Abstract : Objective: Ribonucleotide reductase (RNR) supplies deoxyribonucleotide diphosphates demanded by cells to repair radiation-induced DNA damage. Here, we investigate the impact of pretherapy RNR M1, M2, and M2b (p53R3) subunit level upon human cervical cancer radiochemosensitivity. Materials/Methods: Immunohistochemistry was performed on a tissue array comprised of 18 paired benign uterine cervix and stage IB2 cervical cancers to evaluate the relationship between cytosolic RNR M1, M2, and M2b staining intensity and radiochemotherapy cancer response. Patients underwent surgical hysterectomy (n = 8), or daily radiation (45 Gy), coadministered once-weekly cisplatin (40 mg/m 2 ), then low–dose rate brachytherapy (30 Gy) followed by adjuvant hysterectomy (n = 10). Radiochemotherapy response was determined by Response Evaluation Criteria In Solid Tumors version 1.0 criteria during brachytherapy. Cancer relapse rates and disease-free survival were calculated. Results: M1, M2, and M2b antibody staining intensity was low (0–1+) in benign uterine cervical tissue. M1 and M2b immunoreactivity was 2+ or 3+ in most (13/18) cervical cancers. M2 immunoreactivity was 3+ in nearly all (16/18) cervical cancers. Cervical cancers overexpressing M1 and M2b had an increased hazard for incomplete radiochemotherapy response, relapse, and shortened disease-free survival. Conclusions: Ribonucleotide reductase subunit levels may predict human cervical cancer radiochemosensitivity and subsequent posttherapy cancer outcome. Further validation testing of RNR subunits as biomarkers for radiochemotherapy response is warranted.